Manajemen Usahatani Padi Sawah di Kabupaten Bone Balango - Adrian Buna; Siti Lofita Ahmad; Septiana Walaji; Rizki Moilo (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2025)
Irrigated rice cultivation continues to be crucial in fulfilling food requirements in Indonesia. Numerous initiatives to enhance rice farming management have been persistently pursued by both farmers and the government. This study aims to examine the management of rice cultivation in Bone Bolango Regency, Gorontalo. The research methodology is descriptive quantitative, displaying the findings using frequency distribution tables. The respondents of the study are rice farmers in Bone Bongalo Regency. The findings indicate that the rice farmers in Bone Bongalo Regency implement management functions in rice cultivation, specifically regarding agricultural technology utilization, production marketing, labour organization, planting and fertilization, and rice cropping systems. Collaboration among members and the agricultural farmers’ group has greatly improved the management of rice farming. Then the farmer’s productivity and revenue can rise in response.